Proceedings of the 6th Augmented Human International Conference 2015
DOI: 10.1145/2735711.2735797
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting spatial skills with semi-immersive interactive desktop displays

Abstract: 3D stereoscopic displays for desktop use show promise for augmenting users' spatial problem solving tasks. These displays have the capacity for different types of immersion cues including binocular parallax, motion parallax, proprioception, and haptics. Such cues can be powerful tools in increasing the realism of the virtual environment by making interactions in the virtual world more similar to interactions in the real non-digital world [21,32]. However, little work has been done to understand the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…A significant fraction of previous fNIRS work has been dedicated to passive acquisition of user cognitive states [40], which has been used to assess cognitive workload [18], information presentation [32], or level of difficulty [13]. This has been applied to usability studies [17] and the development of adaptive interfaces [14], for instance through dynamic difficulty adjustment [2], recommender systems [31], or new pointing techniques [3].…”
Section: Previous and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant fraction of previous fNIRS work has been dedicated to passive acquisition of user cognitive states [40], which has been used to assess cognitive workload [18], information presentation [32], or level of difficulty [13]. This has been applied to usability studies [17] and the development of adaptive interfaces [14], for instance through dynamic difficulty adjustment [2], recommender systems [31], or new pointing techniques [3].…”
Section: Previous and Related Workmentioning
confidence: 99%
“…The rapid progress of fNIRS applications to user interfaces makes it possible to envision a new generation of Brain-Computer Interfaces (BCI), with improved spatial resolution, better signal stability and greater robustness to motion artefacts [1,40]. One particular interest for the development of BCI is the accessibility of specific prefrontal areas to fNIRS [11,29,43].…”
Section: Introductionmentioning
confidence: 99%
“…Although initial evaluations using the zSpace have been already done [33], future work could include user studies, examining the combination of hybrid-dimensional visualization and navigation techniques.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…During the virtual training both VR training groups reported comparable levels of workload. Previous research showed that multisensory cuing as well the immersive properties of the VR environment can contribute to increased cognitive workload [ 25 , 43 , 61 , 63 ]. As both VR training groups reported high levels of presence during virtual training, with high levels of involvement and immersion, it is therefore plausible that these factors also contributed to their perceived workload levels.…”
Section: Discussionmentioning
confidence: 99%